Psychological and behavioral adjustment in female youths with high or low psychopathic traits - Pechorro, Pedro Fernandes dos Santos (2014)
The aim of the present study was to analyze the role of psychopathic traits in female juvenile delinquency. Using a sample of 236 young females from the Juvenile Detention Centers of the Portuguese Ministry of Justice and schools in the Lisbon area, a group of female youths with high psychopathic traits (n = 118; M = 15.84 years of age; range = 14–18 years of age) and a group of female youths with low psychopathic traits (n = 118; M = 15.77 years of age; range = 14–18 years of age) were formed based on the Portuguese version of the Antisocial Process Screening Device-Self-report (APSD-SR). The results showed that young females with high psychopathic traits start engaging in criminal activities and come into contact with the justice system earlier in life; exhibit higher levels of behavioral problems, conduct disorder, delinquent behaviors and serious criminality; and demonstrate lower levels of self-esteem and pro-social behavior. The importance of some variables in predicting group membership (high versus low psychopathic traits) was established through a binary logistic regression. Our findings reinforce the importance of the psychopathy construct for the early identification of potentially high-risk female youths and for the assessment of female youths who have already come into contact with the judicial system.